STRATEGI PEMASARAN DAN PENINGKATAN JUMLAH KUNJUNGAN PASIEN DALAM UPAYA MENINGKATKAN PROFIT RUMAH SAKIT - Fidyaningsih, Ririk (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
In today's competitive era, hospitals are faced with challenges to not only provide quality health services, but also to increase their profitability. Effective marketing strategies and improving patient services are crucial aspects in achieving this goal. In the context of increasingly competitive health services, hospitals need to implement an integrated marketing strategy utilizing the 7 P marketing mix. This literature review aims to analyze hospital marketing strategies. The method for writing this scoping review uses a systematic data search method. The data was collected using the keyword Hospital Marketing Strategy from online literature such as Google Scholar published in 2022-2024, after which it was reviewed based on the results of the inclusion and exclusion criteria; there were 5 articles used. The results and conclusions of this research are that effective marketing strategy implementation lies in a holistic and integrated approach. By understanding patient needs and preferences, hospitals can design relevant, high-quality services, while digital marketing and engaging promotions help reach a wider audience. A positive patient experience supported by friendly service and efficient processes will drive loyalty and word of mouth recommendations. Additionally, offering competitive service packages can attract new patients. By optimizing all these aspects in their marketing strategy, hospitals can not only increase the number of patient visits but also ensure sustainable revenue growth and long-term success.